AC Loss Measurements of a Trapezoidal Shaped HTS Coil Using an Electrical Method. (2nd December 2014) - Messina, G.; Morici, L.; Besi Vetrella, U.; Celentano, G.; Marchetti, M.; Viola, R.; Sabatino, P.
Abstract : High temperature superconducting (HTS) coils of different shapes (typically circular or trapezoidal) wound on iron or ironless core are fundamental components of many superconducting electrical power devices. A 150-turn (75 turns/pancake) trapezoidal coil in double pancake configuration has been designed and realized in our laboratory of ENEA Frascati. Various epoxy resins and YBCO tapes have been tested in the temperature range room to liquid nitrogen, leading us to the choice of AmSC (American Superconductor) tape for the winding and araldite resin for the impregnation process. The trapezoidal shape has been chosen because of its suitable geometry for practical applications, the results being complementary to what was previously achieved on round shaped HTS coils. The AC transport current losses have been measured using a compensated electrical method and expressed in terms of a linearly frequency dependent resistance. A linear dependence of the losses resistance from frequency was expected and found in agreement with previous results. The current-voltage curve has been measured in zero externally applied field condition, the results being in good agreement with a numerical simulation. The magnetic field distributions, at different air gaps from coil top and zero externally applied filed condition, have been simulated and reported as well.